New insights into the support morphology-dependent ammonia synthesis activity of Ru/CeO2 catalysts. Issue 1 (7th December 2016) - Ma, Zhanwei; Zhao, Shengli; Pei, Xiaoping; Xiong, Xumao; Hu, Bin
Abstract : Different morphologies ceria (nanocubes, nanorods and nanoparticles) were synthesized and exhibited significant support-morphology-dependent catalytic activity towards ammonia synthesis. Abstract : Three ceria nanocrystals with different morphologies (nanocubes, nanorods, and nanoparticles) were synthesized and used as supports to evaluate the support morphology-dependent ammonia synthesis activity in the structure-sensitive ammonia synthesis reaction. The Ru/r-CeO2 catalyst shows a higher catalytic reaction rate (3830 μmol g −1 h) than that of Ru/c-CeO2 (1289 μmol g −1 h) and Ru/p-CeO2 (529 μmol g −1 h) under the reaction conditions of 400 °C, 1 MPa, and 60 mL min −1 . In addition, promoters (Cs, K, and Ba) can effectively enhance the catalytic activity of the catalysts such as 2Cs–Ru/r-CeO2 (14 266 μmol g −1 h) and 2K–Ru/r-CeO2 (11 227 μmol g −1 h). The effect of the morphology of the CeO2 support on the metal–support interaction and catalytic performance of the Ru/CeO2 catalysts can be correlated to the exposed crystal planes and surface composition/electronic structure of the CeO2 support with diverse morphologies.